Short-Term Exposure of Paddy Soil Microbial Communities to Salt Stress Triggers Different Transcriptional Responses of Key Taxonomic Groups - Peng, Jingjing; Wegner, Carl-Eric; Liesack, Werner (Frontiers in Microbiology, 2017)
Soil salinization due to seawater intrusion along coastal areas is an increasing threat to rice cultivation worldwide. While the detrimental impact on rice growth and yield has been thoroughly studied, little is known about how severe salinity affects structure and function of paddy soil microbial communities. Here, we examined their short-term responses to half- and full-strength seawater salinity in controlled laboratory experiments. Slurry microcosms were incubated under anoxic conditions, with rice straw added as carbon source. Stress exposure time was for 2 days after a pre-incubation period of 7 days. Relative to the control, moderate (300 mM NaCl) and high (600 mM NaCl) salt stress suppressed both net consumption of acetate and methane production by 50% and 70%, respectively. Correspondingly, community-wide mRNA expression decreased by 50% to 70%, with significant changes in relative transcript abundance of family-level groups. mRNA turnover was clearly more responsive to salt stress than rRNA dynamics. Among bacteria, Clostridiaceae were most abundant and the only group whose transcriptional activity was strongly stimulated at 600 mM NaCl. In particular, clostridial mRNA involved in transcription/translation, fermentation, uptake and biosynthesis of compatible solutes, and flagellar motility was significantly enriched in response salt stress. None of the other bacterial groups were able to compete at 600 mM NaCl. Their responses to 300 mM NaCl were more diverse. Lachnospiraceae increased, Ruminococcaceae maintained, and Peptococcaceae, Veillonellaceae, and Syntrophomonadaceae decreased in relative mRNA abundance. Among methanogens, Methanosarcinaceae were most dominant. Relative to other family-level groups, salt stress induced a significant enrichment of transcripts related to the CODH/ACS complex, methanogenesis, heat shock, ammonium uptake and thermosomes, but the absolute abundance of methanosarcinal mRNA decreased. Most strikingly, the transcriptional activity of the Methanocellaceae was completely suppressed already at 300 mM NaCl. Apparently, the key taxonomic groups involved in the methanogenic breakdown of plant polymers significantly differ in their ability to cope with severe salt stress. Presumably, this different ability is directly linked to differences in their genetic potential and metabolic flexibility to reassign available energy resources for cellular adaptation to salt stress.